Risk factors and outcome associated with coinfection with carbapenem-resistant Klebsiella pneumoniae and carbapenem-resistant Pseudomonas aeruginosa or Acinetobacter baumanii: a descriptive analysis - Sophonsri, Anthony; Kelsom, Corey; Lou, Mimi; Nieberg, Paul; Wong-Beringer, Annie (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Nearly 30% of patients infected with carbapenem-resistant Klebsiella pneumoniae (CRKP) were previously shown to be coinfected with carbapenem-resistant Pseudomonas aeruginosa (CRPA) or Acinetobacter baumannii (CRAB). Infections caused by multiple carbapenem-resistant pathogens present significant challenge to infection control and therapeutic management. The study objective was to identify risk factors for acquisition of multiple carbapenem-resistant pathogens and associated outcomes.Methods: A descriptive analysis of adults infected with either CRKP alone or coinfected with CRPA or CRAB was performed. Patient groups were compared on demographics, clinical characteristics, treatment, and outcome.Results: 86 patients with CRKP monoinfection and 60 patients with coinfections were evaluated.Respiratory tract was the predominant infection site for coinfected patients involving mostly CRPA whereas urinary tract was the primary site for CRKPonly group. More coinfected patients were severely debilitated, had prior carbapenem exposure (37% vs 13%, p<0.001) and history of pneumonia in the past year (67% vs 41%, p<0.01). More coinfected patients required direct ICU admission (45% vs 27%, p=0.02) and had prolonged length of stay (median 15 vs 10 days, p<0.01) than the CRKP only group but mortality rates (18% vs 16%) were similar.Conclusions: CRKP coinfection with another carbapenem-resistant pathogen adds significant morbidity and healthcare burden overall. Empiric therapy with reliable activity against both CRKP and carbapenem-resistant Pseudomonas aeruginosa may be prudent for at risk patients with pneumonia.